Strategie chroniące ego – analiza motywacyjna na przykładzie self-handicapping i defensive pessimism - Więckowska, Aleksandra (Neofilolog, 2010)
In traditional classrooms, where students are evaluated on the basis of their actions, poor performance is closely linked to the lack of ability. Many students often see failure as a threat to their positive self-image and instead of increasing efforts, apply various ego-protective strategies to shift attention from real or hypothesized lack of ability to other factors influencing unsatisfactory production. In both cases self-worth is protected. This paper aims at performing a motivational analysis of two such strategies, i.e. self-handicapping and defensive pessimism used by secondary school students in achievement context.